Improving Prescribing through User-Centered Design: Design Guide and Interface Examples for Anticoagulant Medication Alerts. Issue 1 (March 2023) - Jacob Seagull, F.; Lanham, Michael; Pomorski, Michelle; Callahan, Mollie; Barnes, Geoffrey D.
Direct Oral Anticoagulants (DOACs) are beneficial blood-thinning medications that are frequently misprescribed. Clinical decision support systems can be effective in reducing these prescription errors through well-designed medication alerts. The effectiveness of alerts can be improved through a User Centered Design (UCD) process. We describe the multi-stage UCD process used to (1) produce initial draft alerts, (2) refine the designs, and (3) validate the designs and findings. The resulting prototype DOAC prescribing alert design is presented with annotations of design principles that were derived and applied. The principles of design for these DOAC medication alerts may be relevant more broadly to the design of other medication alerts.